2023
DOI: 10.1177/09564624221149770
|View full text |Cite
|
Sign up to set email alerts
|

The burden of chlamydia, gonorrhea, and syphilis in older adults in the United States: A systematic review

Abstract: Background Increases in life expectancy, the availability of sexual performance enhancing medication, and changes in sexual partnering suggest that sexually transmitted infections (STIs) among older persons could be on the rise, yet there have been relatively few studies examining STIs in this demographic. Our systematic review aimed to further characterize the incidence and prevalence of chlamydia, gonorrhea, and syphilis, along with associated risk factors among older adults (45 years or older) in the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…These groups had received comparatively less attention. In a study conducted in the United States, a similar finding was reported, revealing an increase in the burden of syphilis among older adults; notably, this population has always been overlooked or neglected 11 .…”
Section: Introductionsupporting
confidence: 66%
“…These groups had received comparatively less attention. In a study conducted in the United States, a similar finding was reported, revealing an increase in the burden of syphilis among older adults; notably, this population has always been overlooked or neglected 11 .…”
Section: Introductionsupporting
confidence: 66%
“…In higher-income countries, syphilis infection is less common and occurs disproportionately in racial, ethnic, and sexual minority populations [ 2 ]. However, recently, an unexpected increase in syphilis has been seen, particularly in populations that had previously received comparatively less attention or were overlooked [ 3 ], such as in women, congenital syphilis [ 4 , 5 , 6 , 7 ], and syphilis in older adults [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%